2021
DOI: 10.1186/s12889-021-10429-0
|View full text |Cite
|
Sign up to set email alerts
|

Trend analysis of cardiovascular disease mortality, incidence, and mortality-to-incidence ratio: results from global burden of disease study 2017

Abstract: Background Cardiovascular diseases (CVDs) are one of the global leading causes of concern due to the rising prevalence and consequence of mortality and disability with a heavy economic burden. The objective of the current study was to analyze the trend in CVD incidence, mortality, and mortality-to-incidence ratio (MIR) across the world over 28 years. Methods The age-standardized CVD mortality and incidence rates were retrieved from the Global Burde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
227
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 408 publications
(237 citation statements)
references
References 45 publications
2
227
0
8
Order By: Relevance
“…Finally, Amini et al used the data from the GBD 2017 study to determine the longitudinal association between cardiovascular disease burden (including incidence and mortality rates) and HDI. They found that developed countries had sharper descending slope of incidence and mortality rates than developing countries (19). In a study by Joseph et al, they declared that although the global CVD mortality has decreased in many parts of the world, the absolute number of deaths is growing in some other regions, especially in low and middle income countries (20).…”
Section: Insert Tablementioning
confidence: 99%
“…Finally, Amini et al used the data from the GBD 2017 study to determine the longitudinal association between cardiovascular disease burden (including incidence and mortality rates) and HDI. They found that developed countries had sharper descending slope of incidence and mortality rates than developing countries (19). In a study by Joseph et al, they declared that although the global CVD mortality has decreased in many parts of the world, the absolute number of deaths is growing in some other regions, especially in low and middle income countries (20).…”
Section: Insert Tablementioning
confidence: 99%
“…Liver disease is a common and increasing cause of morbidity and premature mortality in the UK and globally (1). This is in contrast to other common chronic diseases such as heart disease where reduction in morbidity and mortality has been seen over the last 50 years (2). The main causes of liver disease in the UK are alcohol related liver disease (ARLD) and non-alcohol related fatty liver disease (NAFLD); which is increasing in parallel with the obesity and Type 2 diabetes (T2DM) epidemics seen in the UK and across the globe (3).…”
Section: Introductionmentioning
confidence: 99%
“…Globally, there were nearly 523.2 million new cases and 18.6 million deaths from CVD in 2019. Its incidence has increased by 17.1% over the past decade [1,2]. In China, CVD is the leading cause of overall death (40% of all disease mortality) [3].…”
Section: Introductionmentioning
confidence: 99%